Pengembangan Media Pembelajaran Pada Materi Pecahan Berbasis Etnomatematika: Development Of Learning Media On Fractions Based On Ethnomathematics - Lestari, Karmila Ayu (Journal of Mathematics Learning Innovation, 2025)
This research focuses on creating educational resources for fraction topics through the lens of ethnomathematics, incorporating elements of local Bugis culture via traditional cakes such as katirisala, Sikaporo, and cucuru’ bayao. The approach utilized in this study is Research and Development (R&D) following the ADDIE model, which encompasses Analysis, Design, Development, Implementation, and Evaluation. Data were gathered using a combination of observation, interviews, surveys, tests, and documentation, which were then analyzed to evaluate the media's validity, practicality, and effectiveness. Expert evaluations revealed a very favorable feasibility rating, with media experts giving a score of 96.66% and material experts providing a score of 83.33%. The practicality assessment indicated that the media fell into a practical category, obtaining an average rating of 79.76% from students and a perfect score of 100% from teachers. The media's effectiveness was evidenced by an N-Gain value of 0.88, classifying it in the high category, which shows a considerable improvement in students' grasp of the concept of equivalent fractions. These outcomes suggest that the fraction learning media based on ethnomathematics is not only valid and practical but also effective in enhancing students’ educational performance. This suggests that the media can serve as a creative alternative for teaching mathematics in elementary schools while also reflecting local cultural heritage.